2016
DOI: 10.1089/jamp.2015.1228
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Cystic Fibrosis Bronchial Secretion and in Vitro Drug Permeation Study: The Effect of Sodium Bicarbonate

Abstract: The interesting results confirm the previously reported bicarbonate. effectiveness in CF; this weak base seems to act by decreasing high viscosity of the CF bronchial secretion and, potentially, resulting in better mucus clearance and in fighting pulmonary infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
4
25
0
1
Order By: Relevance
“…Therefore, increasing the frequency of NaHCO 3 inhalations should be tested (every 4-6 h dosing); considering that most patients are prescribed airway clearance therapy two to three times per day, more frequent bicarbonate dosing may be feasible, but a search for alternative formulations that might allow a longer duration of action seems justifiable. A corroborating increase in pH due to NaHCO 3 in vitro has been described [15].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Therefore, increasing the frequency of NaHCO 3 inhalations should be tested (every 4-6 h dosing); considering that most patients are prescribed airway clearance therapy two to three times per day, more frequent bicarbonate dosing may be feasible, but a search for alternative formulations that might allow a longer duration of action seems justifiable. A corroborating increase in pH due to NaHCO 3 in vitro has been described [15].…”
Section: Discussionmentioning
confidence: 60%
“…In a study on the effect of mixing NaHCO 3 solution directly with the sputum of CF patients in vitro, Stigliani et al [15] reported reductions in rheological moduli G′, G″, and G*. However, the present study evaluated native expectorated sputum.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Micro-rheological properties of CF sputum [85] have been investigated using techniques such as diffusion rates or behavior of a tracer (molecules, peptides, nanospheres and microspheres) using fluorescence recovery after photobleaching, dynamic light scattering, fluorescence correlation spectroscopy and single-particle tracking in multi-particle tracking experiments [86]. These experiments and biochemical analyses have demonstrated that sputum microstructure is significantly altered by elevated mucin and extracellular DNA content.…”
Section: Discussionmentioning
confidence: 99%
“…However, in that early work, the donor compartment of the diffusion system contained a non-physiologic large volume of drug solution. Two decades later, the permeation of gentamicin sulfate [9] and ketoprofen lysinate [10] formulated as inhalation dry powders was reported to be significantly delayed in modified Franz cells when these incorporated a layer of artificial cystic fibrosis mucus or cystic fibrosis sputum, respectively. A common limitation of the three aforementioned studies is that the thickness of the mucus layers (~3 mm) was not clinically representative.…”
Section: Introductionmentioning
confidence: 99%